2022
DOI: 10.1111/dpr.12612
|View full text |Cite
|
Sign up to set email alerts
|

Rural mechanization for equitable development: Disarray, disjuncture, and disruption

Abstract: Motivation: Agricultural mechanization was once a mainstream issue.From the 1990s onwards it received less priority, as public policy concern for equitable economic development in rural areas faded. Despite recent signs of renewed interest, questions of rural mechanization require more systematic attention. After a long period of neglect, our knowledge is in disarray. Purpose: This article traces the evolution of thinking about rural mechanization. It examines how three increasingly important factors affect or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Technological advancement has been a primary driving force in enhancing agricultural productivity and supporting agricultural growth (Liu et al, 2020). From on-farm operations to off-farm activities, agricultural mechanization has been identified as a crucial factor in increasing agricultural productivity and promoting rural sector industrialization, as well as the overall economic development of nations (Lewis et al, 2022). Agricultural mechanization is also considered to heavily impact the supply and demand of labour and agricultural profitability, hence serving as a backbone for every thriving agricultural economy (Peng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Technological advancement has been a primary driving force in enhancing agricultural productivity and supporting agricultural growth (Liu et al, 2020). From on-farm operations to off-farm activities, agricultural mechanization has been identified as a crucial factor in increasing agricultural productivity and promoting rural sector industrialization, as well as the overall economic development of nations (Lewis et al, 2022). Agricultural mechanization is also considered to heavily impact the supply and demand of labour and agricultural profitability, hence serving as a backbone for every thriving agricultural economy (Peng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the evolution of agricultural mechanisation, D. Lewis et al (2022) identified the most influential factors: the expansion of input markets; the development of urban-rural linkages; and the climate crisis. The authors drew attention to the need to formulate policies for the development of mechanisation of small farms and small and medium-sized enterprises by taking into account local and national characteristics, obtaining proposals from various sources, and creating a database of these enterprises, in particular through public-private partnership experiments.…”
Section: Introductionmentioning
confidence: 99%